Pengaruh Pengelolaan dan Penggunaan Dana Desa terhadap Kesejahteraan Masyarakat Desa Bandar Labuhan - Wan Dian Safina; Ade Novita Sari (Al-Buhuts, 2022)
This study aims to determine whether there is an influence of the management and use of village funds on community welfare, in the village of Bandar Labuhan, Kec. Tanjung Morawa, Deli Serdang Regency. The research method used in this research is a quantitative method with a descriptive approach. The population in this study is the community in Bandar Labuhan Village, Kec. Tanjung Morawa Deli Serdang Regency as many as 1899 heads of families with a sample of 94 households. The instrument used was a questionnaire, with data analysis techniques using correlation coefficient analysis. Based on the results of partial hypothesis testing (t-test), it is known that the t variable X1 is 2.122 greater than t table 1.661 (2.122> 1.661), X2 is 7.147 greater than t table 1.661 (7.147> 1.661) so it can be concluded that management and the use of Village Funds has a significant effect on the Welfare of the Bandar Labuhan Village Community.